2011
DOI: 10.5005/jp-journals-10013-1066
|View full text |Cite
|
Sign up to set email alerts
|

Should Voriconazole be the Primary Therapy for Chronic Invasive Sinus Aspergillosis (CISA)?

Abstract: Background: The endonasal endoscopic surgery has stood the test of time in managing inflammatory as well as other diseases affecting nose and paranasal sinuses.Objective: To report our experience with endonasal endoscopic surgery of benign tumors and tumor-like conditions of the nose and paranasal sinuses. Methods:The medical records of 92 patients with tumors and tumor-like conditions, who had undergone endoscopic surgery for removal of their lesions between 1999 and 2010, were retrospectively studied. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Figure 2 presents the results of the systematic bias analysis. There was a low risk of bias for most items, except for the presence of performance and detection bias due to the lack of a double-blind design and blind outcome assessment in four studies [ 18 , 22 , 27 , 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 presents the results of the systematic bias analysis. There was a low risk of bias for most items, except for the presence of performance and detection bias due to the lack of a double-blind design and blind outcome assessment in four studies [ 18 , 22 , 27 , 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Nephrotoxicity could be analyzed for 9 RCTs involving 2530 patients [ 20 22 , 28 – 32 ]. The rate of the abnormal renal function was significantly lower in the VRC group than in the counterparts group (10.0% vs. 17.1%) (OR = 0.46, 95% CI = 0.26–0.84, P = 0.02; I 2 = 67%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In their study with treatment with voriconazole, Bansal and Gupta reported that many patients developed skin rashes on voriconazole, but were transient and did not hamper the administration of voriconazole to the patients and disappeared after the stopping of the drug. 52 Invasive fungal sinusitis is on the rise worldwide and especially in North India as it is endemic in this part of the country. It is affecting immunocompetent young and middle aged population causing a great morbidity and mortality.…”
Section: Aijcrmentioning
confidence: 99%
“…The results were not favorable with voriconazole in the intradural involvement probably due to the treatment duration of 14 weeks only (Figs 5 and 6). 52 A treatment of 6 to 12 months is being advocated in skull base aspergillosis these days. 15,16 Rhinocerebral aspergillosis carries a high mortality, especially in immune-suppressed patients and after bone marrow transplantation.…”
Section: Aijcrmentioning
confidence: 99%